2007
DOI: 10.1111/j.1365-2958.2007.05593.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial regulation of ospC expression in Borrelia burgdorferi

Abstract: SummaryOuter surface lipoprotein (Osp) C is a virulence factor required for transmission of the Lyme disease agent, Borrelia burgdorferi. We have constructed an inducible promoter system to study the function and regulation of OspC by integrating regulatory elements from the Escherichia coli lac operon into the B. burgdorferi genome. An inducible promoter (flacp) was constructed by inserting a synthetic lac operator sequence between the transcriptional start site and the ribosomal binding site of the B. burgdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
127
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(131 citation statements)
references
References 69 publications
4
127
0
Order By: Relevance
“…However, nothing is known about the regulatory protein or how it is induced during the enzootic cycle of B. burgdorferi. In vitro ospC expression is always associated with the upregulation of RpoS [26,35,36,38], suggesting that the repressor is not induced in vitro. Our previous study showed that deletion of the operator does not influence in vitro ospC expression, thus, ruling out the involvement of the operator-repressor system in ospC regulation [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nothing is known about the regulatory protein or how it is induced during the enzootic cycle of B. burgdorferi. In vitro ospC expression is always associated with the upregulation of RpoS [26,35,36,38], suggesting that the repressor is not induced in vitro. Our previous study showed that deletion of the operator does not influence in vitro ospC expression, thus, ruling out the involvement of the operator-repressor system in ospC regulation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Only three σ factors can be identified from the entire genome of B. burgdorferi, including the major factor, RpoD (σ 70 ), and two alternative factors, RpoN (σ 54 ) and RpoS (σ 38 ) [25]. Moreover, the two alternative factors compose a regulatory network, in which RpoS expression depends on RpoN [26,27], greatly limiting their role in contribution to diverse gene regulation.…”
Section: Introductionmentioning
confidence: 99%
“…OspC has been shown to be required for B. burgdorferi to establish infection in mammals (8,14), as well as for spirochetal transmission from ticks to mammals (15,16). Infectivity studies demonstrate that the ospC mutant cannot establish infection in immunocompetent and SCID mice (lacking B and T cells) when inoculated at a dose of 10 3 to 10 5 spirochetes per mouse (8,(16)(17)(18)(19)(20). The ospC mutant is cleared within the first 48 h of infection in the murine host (21), suggesting a protective role of OspC against innate defenses.…”
mentioning
confidence: 99%
“…burgdorferi promoter (25) linked to bosR (P flacbosR). Cells with reduced BosR have a delayed growth phenotype under all conditions but exhibit restricted cell density under microaerobic conditions.…”
mentioning
confidence: 99%